Study on the Planning of External Lightning Overvoltage Protection for the Universitas Tanjungpura Hospital Building - Alamsyah, Muhammad Reky; Rajagukguk, Managam; Danial, Danial (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
The Tanjungpura University Hospital building is located in the city of Pontianak, which is situated on the equator and often faces the potential of lightning strikes, thus requiring the installation of an external lightning surge protection system. This study aims to design an external lightning surge protection system capable of protecting the Tanjungpura University Hospital building using the rolling sphere method. In the rolling sphere method, calculations will be made for the lightning strike distance (R), protection radius (Rp), protection area (Ax), and determination of protection angle (Î±). The University Tanjungpura Hospital building is at protection level IV, with a current strength of I = 16 kA and a lightning strike distance to the ground of 60.63 meters. The results obtained for using finials with the same height, hp = 1 meter, require hundreds of finials, while using a combination of finials and towers requires 68 finials. In the case of tower finials with a height hp = 10 meters, additional conductor wires are added or the catenary method is used with 14 conductor wires connecting 28 tower finials with a height of 10 meters, due to the areas outside the protection zone between these 28 final towers, necessitating the addition of conductor wires to expand the protection area of the rolling sphere method to protect the areas of the Tanjungpura University Hospital building.